Narrow-Band Ultraviolet B versus Oral Minocycline in Treatment of Unstable Vitiligo: A Prospective Comparative Trial - Amir Hossein Siadat; Naser Zeinali; Fariba Iraji; Bahareh Abtahi-Naeini; Mohammad Ali Nilforoushzadeh; Kioumars Jamshidi; Parastoo Khosravani (Dermatology Research and Practice)
Background. We have compared NB-UVB and oral minocycline in stabilizing vitiligo for the first time. Subjects and Methods. 42 patients were divided equally into two groups: the NB-UVB and minocycline groups. Phototherapy was administered twice a week on nonconsecutive days. In the minocycline group, patients were advised to take minocycline 100 mg once daily. The treatment period was 3 months. Vitiligo disease activity (VIDA) score was noted every 4 weeks for 12 months. Digital photographs were taken at baseline and monthly intervals. Results. Before the therapy, disease activity was present in 100% of the patients, which was reduced to 23.8% and 66.1% by the end of therapy in the NB-UVB and minocycline groups retrospectively (P<0.05). 16 of the 21 (76/1%) patients with unstable disease in the NB-UVB group achieved stability, whereas this was the case for only 7 of the 21 (33.3%) in the minocycline group (P<0.001). The diameter changes were statistically significant at the end of treatment in the NB-UVB group compared to the minocycline group (P=0.031). Side effects in both groups were mild. Conclusion. NB-UVB was statistically more advantageous than oral minocycline in unstable vitiligo in terms of efficacy and the resulting stability.